Perancangan Dan Pembuatan Modul Multimedia Interaktif Berbasis Macromedia Director MX Pada Mata Pelajaran Simulasi dan Komunikasi Digital - Rini Sefriani; Jhon Veri (Universitas Putra Indonesia YPTK Padang, 2021)
This research and development aims to produce products in the form of Learning Media Interactive Multimedia Module Based on Macromedia Director MX for Class X in SMK-SMAK Padang. This research uses the Research and Development (R&D) research method which refers to the 4D Model with the stages passed in this research are the definition stage, the design stage, the development stage, and the deployment stage. Data retrieval is done to the user of the Interactive Multimedia Module. The research sample consisted of 33 people consisting of 32 students and 1 teacher of the subject of Simulation and Digital Communication (SIMKOMDIG) SMK-SMAK Padang. Validity test results by experts Overall assessment of the validator test on Learning Media Interactive Multimedia Module Based on Macromedia Director MX is 90.35%, so that the level of validity can be interpreted very validly used. Overall practicality assessment of learning media Interactive Multimedia Module Based on Macromedia Director MX is 87.72%, so that the level of practicality can be interpreted very practically used. For effectiveness test Overall assessment of the effectiveness of learning media Interactive Multimedia Module Based on Macromedia Director MX at 85.51%, so that the level of effectiveness can be interpreted effectively used. MX has been tested for eligibility, is practically used and is effectively used in the learning process in Simulation and Digital Communication (SIMKOMDIG) subjects at SMK-SMAK Padang.